Aktivitas Antioksidan Minuman Fungsional dari Irisan Buah Kering Mahkota Dewa - Aisyah Tri Septiana; Hidayah Dwiyanti (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2009)
Mahkota dewa (Phaleria macrocarpa (Scheff) Boerl) contains bioactive compounds having antioxidant activity. The aims of the research were to study the influence of processing methods and the kinds of sweetener to the level and activity of antioxidant of beverage from mahkota dewa dried fruit slices. Mahkota dewa beverage with the highest antioxidant level and activity obtained on combination of dipping treatment method and honey sweetener usage. The results showed that the total phenolic content of 11.01 ppm, the inhibition percentage of peroxide of 83.02 %, and the inhibition percentage of malonaldehide (MDA) of 67.54 %. Ability to inhibition forming of the MDA and peroxide bigger than tokoferol.ABSTRAKBuah mahkota dewa (Phaleria macrocarpa (Scheff) Boerl) mengandung zat-zat aktif yang mempunyai aktivitas antioksidan. Penelitian ini bertujuan untuk mengetahui pengaruh metode pengolahan dan jenis pemanis terhadap kadar dan aktivitas antioksidan minuman mahkota dewa. Kombinasi perlakuan terbaik yang memiliki kadar dan aktivitasantioksidan paling tinggi adalah kombinasi perlakuan perendaman dan jenis pemanis madu yang ditunjukkan dengannilai total fenol sebesar 11,01 ppm, penghambatan peroksida sebesar 83,02 %, dan penghambatan malonaldehida(MDA) sebesar 67,54 %. Kemampuan terhadap penghambatan pembentukan peroksida dan MDA tersebut lebih besardari α tokoferol.